Planning in uncharted waters: Spatial transformations, planning transitions and role-reflexive planning; Planung in unbekannten Gewässern: Räumliche Transformationen, Planungswandel und rollenreflexive Planung - Christian Lamker (Raumforschung und Raumordnung / Spatial Research and Planning, 2019)
For planners, processes of complex spatial transformations today are comparable to uncharted land and an uncertain voyage. Many possible role images overlap and contrast to traditional and established ways of thinking and acting. The focus here is on navigating instead of controlling, about supporting instead of enforcing. Planning lacks tools to think and act when facing uncertainty. This paper proposes role-reflexive planning as an educational and experimental approach to thinking through different potentialities. It offers groundwork from the boundary between planning and transition studies, using role-based ideas as a bridge. It offers an overview about different roles that are relevant to working towards transformations as spatial planners. It develops an account of role-reflexive planning that connects between contexts, actions and back to individual modes of behaviour in planning processes. As a basis, this paper condenses experiences of a role-playing pilot workshop and discussions about potential elements of a transition towards "post-growth planning". It outlines how role-playing challenges the individual roles of actors beyond the game situations themselves. Conceptual ideas foster a renewed role-based debate on thinking and acting in the face of uncertainty and ways to navigate through the stormy waters of transformation. – – Prozesse komplexer räumlicher Transformationen sind für Planer vergleichbar mit einem unerforschten Land oder einer ungewissen Reise. Viele mögliche Rollenverständnisse überlagern sich und stehen traditionellen und etablierten Denk- und Handlungsweisen gegenüber. Dabei geht es um Navigieren statt Kontrollieren, um Unterstützen statt Durchsetzen. In der Planung fehlen hingegen geeignete Werkzeuge, um bei Unsicherheit zu denken und zu handeln. Dieser Beitrag arbeitet rollenreflexive Planung als pädagogischen und experimentellen Ansatz heraus. Er bietet Grundlagen an der Schnittstelle von räumlicher Planung zur Transitionsforschung unter Verwendung rollenbasierter Ideen als Brücke. Er enthält einen Überblick über unterschiedliche Rollenverständnisse, die für Planung für und mit Transformationen für Planer relevant sind. Er entwickelt eine rollenreflexive Planung, die zwischen Kontext und Handlungen vermittelt sowie mit individuellem Verhalten in Planungsprozessen verbindet. Als Grundlage arbeitet der Beitrag Erfahrungen aus einem Rollenspiel in einem Pilotworkshop zur Transition zu einer Postwachstumsplanung auf. Er umreißt, wie Rollenspiele die eigenen Rollen von Akteuren über die individuelle Spielsituation hinaus herausfordern. Konzeptionelle Ideen fördern eine erneuerte rollenbasierte Debatte über Denken und Handeln unter Unsicherheit und Wege, durch stürmische Gewässer von Transformationen zu navigieren.
Keywords: 710; Role of planners; role reflection; role-based approach; Rolle von Planern; Rollenreflexion; rollenbasierter Ansatz